Whole exome sequencing identifies a mutation for a novel form of corneal intraepithelial dyskeratosis - Maurer-Stroh, Sebastian (2013)
Background Corneal intraepithelial dyskeratosis is an extremely rare condition. The classical form, affecting Native American Haliwa-Saponi tribe members, is called hereditary benign intraepithelial dyskeratosis (HBID). Herein, we present a new form of corneal intraepithelial dyskeratosis for which we identified the causative gene by using deep sequencing technology.